PREFERENCES OF SERBIAN CONSUMERS TOWARDS DIFFERENT PEPPER FRUITS - Danojević, Dario Đ; Glogovac, Svetlana; Medic-Pap, Sladjana; Moravcevic, Djordje (Food and Feed Research, 2021)
Pepper (Capsicum annuum L.) is one of the major vegetable species in the world. In Balkan cuisines, as well as in Serbia, pepper has a very diverse use. Knowledge about consumer preferences is of great importance for a breeding process as well as in the market-orientated production. Because of the lack of information about consumer preferences towards pepper types, in the Serbian market, the present research was conducted. Four hundred and two participants, classified into groups, according to gender, age and education, answered the survey questions. According to this research, the most preferred pepper type in Serbia is kapia, while the bell pepper is the second chosen type. Also, it was revealed that the most favourite colour of pepper fruit is red. There is a tendency for higher importance of fruit type rather than fruit colour. The highest percentage of hot pepper consumers prefers medium hot peppers. The obtained trend shows that women generally prefer less spicy pepper fruits than men.